(untitled) (Progress Annals: Journal of Progressive Research, 2024)
a plate handle that connects fixed mirrors for car windscreens plays an important role in ensuring the safety and comfort of vehicles. This handle, by tying the mirrors firmly, increases their performance and protects against shocks when in motion. Fixed mirrors allow safe movement by expanding the driver’s field of view. The material and design of the plate handle helps to ensure the long-term operation of the mirrors, as well as increase resistance to the influence of the internal and external environment. Thus, this handle has a positive effect on the overall appearance of the car, not only functionally, but also aesthetically.